OPTIMIZING PERFORMANCE THROUGH EMPLOYEE PLANNING - Yessi Indra; Sri Rahayu; Kiki Farida Ferine (Universitas Efarina, 2025)
This study aims to analyze the effect of Organizational Climate and Work Ethics on Employee Performance with Employee Planning as a mediating variable. The research was conducted in an institution involving 86 respondents. The study applied a quantitative approach using Partial Least Square–Structural Equation Modeling (PLS-SEM). The results indicate that Work Ethics has a positive and significant effect on Employee Performance and also significantly influences Employee Planning. Organizational Climate does not have a direct effect on Employee Performance, but it has a significant positive effect on Employee Planning. Furthermore, Employee Planning significantly affects Employee Performance. As a mediator, Employee Planning significantly mediates the relationship between Work Ethics and Employee Performance, but it does not mediate the effect of Organizational Climate on Employee Performance. These findings emphasize the importance of improving employee planning to enhance performance through work ethics.